Critical systems heuristics - Ulrich, Werner; Reynolds, Martin (Systems Approaches to Manging Change: A Practical Guide, 2010)
This chapter provides a detailed introduction to critical systems heur istics and the use of its central tool boundary critique. What Is CSH? Two Studies in Applying CSH Using CSH as an Intervention Tool: Some B asic Concepts A Core Concept of CSH: Systematic Boundary Critique Boun dary Critique Applied to NRUA-Botswana Boundary Critique Applied to EC OSENSUS-Guyana Boundary Critique and Personal Competence Recognising B oundary Judgements – and Keeping Them Fluid Towards a New Ethos of Pro fessional Responsibility